Ayurvedic Perspective of Recurrent Pregnancy Loss (AYUSHDHARA, 2022)
Recurrent Pregnancy Loss (RPL) is defined as two or more failed clinical pregnancies confirmed by sonography or histopathology. In majority of patients the etiology cannot be clearly defined, so it is one of the arduous and composite area in the medical field for both doctors and patients to handle. The etiology of Recurrent Pregnancy Loss can be broadly included under genetic, endocrine, anatomic, environmental and immunological factors. As this is a multifactorial entity and is difficult to pinpoint a specific etiology or pathology in majority of cases, a thorough and detailed history taking along with necessary investigations have to be done. Treatment mainly aims in rectifying the cause and psychological support together with counselling in couples with unknown causes will improve the outcome. In Ayurveda Recurrent Pregnancy Loss can be correlated with Garbhasravi vandhya mentioned in Hareetha samhitha and Puthraghni yonivyapth explained in Brhathtrayees based on the clinical features. Ayurveda advises to do Sodhana therapy (purificatory procedures) ending with Uthara vasti in Recurrent miscarriage cases especially with unknown etiology. Acarya Hareetha and Acarya Caraka explained Garbhasravi vandhya and Puthragni yonivapath respectively as loss of pregnancy occurring in first trimester. Susruta says that in this condition, the foetuses after attaining stability are repeatedly destroyed due to bleeding which indicates second trimester abortions. On conclusion both Garbhasravi vandhya and Puthraghni yonivyapath can be considered as Recurrent Pregnancy loss explained in modern science.